1982
DOI: 10.3758/bf03212286
|View full text |Cite
|
Sign up to set email alerts
|

Polydipsia and autoshaping: Drinking and leverpressing as substitutes for eating

Abstract: Three experiments delivered food at fixed or random intervals independently of the rat's behavior, always less than the amount eaten with food freely available. The results revealed a polydipsicresponse to this experimental suppression of eating, and total drinking decreased as total eating increased. When we added a lever that signaled each food delivery, leverpressing and drinking rose far above their baseline levels; both responses decreased as total eating increased. When a similar schedule presented lever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Thispossibility is supported by research (e.g., Allison & Mack, 1982;Beck, 1964;Collier, 1964) which hasexplicitly examined various foodintakemeasures as a function of amount of water intake. Suchresearch has shown that thepellets-per-dipper functions and the pellets-per-minute functions shown in Figure 2 and the linear relationbetween log food intake versus log water intake shown in Figure 3 are relationships commonly observed in rats exposed to various manipulations of amount of water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thispossibility is supported by research (e.g., Allison & Mack, 1982;Beck, 1964;Collier, 1964) which hasexplicitly examined various foodintakemeasures as a function of amount of water intake. Suchresearch has shown that thepellets-per-dipper functions and the pellets-per-minute functions shown in Figure 2 and the linear relationbetween log food intake versus log water intake shown in Figure 3 are relationships commonly observed in rats exposed to various manipulations of amount of water.…”
Section: Discussionmentioning
confidence: 99%
“…After several researchers reported failure to produce schedule-induction of eating by intermittent water (Carlisle, Shanab, & Simpson, 1972;King, 1974; also see Allison & Mack, 1982 stein (1979) raised the possibility that eating nevertheless might be under the control of intermittent water in terms of temporal patterning. They varied the interwater interval from 30 to 240 sec and found that eating was indeed temporally modulated by the water schedule; this temporal modulation is a characteristic property of SIP.…”
mentioning
confidence: 99%
“…Reprints may be obtained from JenniferJ. Higa, Departmentof Psychology, WashingtonState University, Pullman, sia (Allison & Mack, 1982). Autoshaping wasdiscovered by Brown and Jenkins (1968).…”
mentioning
confidence: 99%
“…Allison and Mack (1982) tested these predictions by varying the total grams of food (NE) delivered during the experimental session. They found that there was a linear increase in Ud and Up as NE decreased.…”
mentioning
confidence: 99%
See 1 more Smart Citation